2007
DOI: 10.1108/14635770710740369
|View full text |Cite
|
Sign up to set email alerts
|

A model for internal benchmarking: when and how?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Some of the largest of these include the National Survey of Student Engagement (NSSE) and its many offshoots ( Barriers to Benchmarking in Higher Education. Whereas benchmarking has become a staple tool for process improvement in business and industry (Southard and Parente, 2007;Stapenhurst, 2009), examples of full-scale benchmarking in higher education are scarce in the literature. It is not hard to identify reasons why benchmarking has failed to gain traction in higher education.…”
Section: Benchmarking In Higher Educationmentioning
confidence: 99%
“…Some of the largest of these include the National Survey of Student Engagement (NSSE) and its many offshoots ( Barriers to Benchmarking in Higher Education. Whereas benchmarking has become a staple tool for process improvement in business and industry (Southard and Parente, 2007;Stapenhurst, 2009), examples of full-scale benchmarking in higher education are scarce in the literature. It is not hard to identify reasons why benchmarking has failed to gain traction in higher education.…”
Section: Benchmarking In Higher Educationmentioning
confidence: 99%
“…Theoretically, intra-institutional benchmarking should encounter fewer barriers than cross-institutional comparisons. Data is more accessible and accurate, and transferring practices is likely to be better accepted because of similarity in culture and environment (Southard and Parente, 2007;Stapenhurst, 2009). Goals for improvement seem more realistic when they are already being accomplished elsewhere in the organization.…”
Section: Are You Ready To Benchmark?mentioning
confidence: 99%
“…In our review of the implementation literature, we found great variation in the detailed steps used by companies in carrying out benchmarking (Bhutta and Huq, 1999;Southard and Parente, 2007;Maire et al, 2005;Binder et al, 2006). For example, Bhutta and Huq (1999) report that some companies have used up to 33 steps, while others have used only four.…”
Section: Benchmarking: Definition and Implementation Approachesmentioning
confidence: 99%
“…Each company seems to employ the number of steps that better suits its individual needs, depending on the complexity and the size of the project that is undertaken. However, despite this variation, the major stages of the benchmarking process remain relatively similar, independently of the amount of attention given to a specific area, which will add or remove a few steps to/from the process (Southard and Parente, 2007;Prasnikar et al, 2005). In this context, two main approaches to benchmarking implementation were identified in the literature: the traditional benchmarking process, associated with the so-called "Traditionalists' perspective"; the diagnostic benchmarking process, associated with the so-called "Modernists' perspective" (Longbottom, 2000).…”
Section: Benchmarking: Definition and Implementation Approachesmentioning
confidence: 99%
See 1 more Smart Citation